Bowel behaviour in young black and white children. Issue 10 (October 1985) - Walker, A R; Walker, B F
Abstract : Bowel behaviour was investigated in 81 rural black, 117 urban black, and 77 white children aged 1 to 4 years. The study was undertaken principally because intake of dietary fibre by urban blacks is now lower than that of whites: moreover, that of rural blacks has also fallen. Average daily defecation frequencies in rural and urban black children and white children were 1.9, 1.8, and 1.5, respectively. Black children voided smaller stools and more frequently than white children. In both ethnic groups most stools were soft. Median transit times, determined in 55 rural black, 80 urban black, and 45 white children, were approximately 6.5, 7, and 27 hours, respectively. Median transit times increased little with age in black compared with white children. The higher defecation frequency and the much shorter transit time in black children are not explicable in terms of the levels of fibre intake.